1949
DOI: 10.1039/tf9494500250
|View full text |Cite
|
Sign up to set email alerts
|

The surface tension of aqueous solutions of ? : ?-dihydroxy-?-aryloxypropanes

Abstract: The surface tensions of various a : p-dihydroxy-aryloxypropanes in aqueous solution have been determined. Substitution of alkyl, alkoxyl and carboalkoxyl groups in the benzene nucleus of the a-phenyl ether of glycerol increases the capillary activity of the parent compound, the effect increasing with increase in the chain-length of the substituent. The increase in capillary activity is greatest with alkyl substituents and least with alkoxyl substituents. The effect of a substituent diminishes in the order : p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1977
1977
1982
1982

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A number of turnover studies have suggested a correlation between rate of turnover and protein subunit size for rat liver soluble and membrane proteins (Dehlinger & Schimke, 1971Dice & Schimke, 1972;Dice et al, 1973;Wang & Touster, 1975;Dean, 1975). In this study no such correlation can be seen in any of the submitochondrial protein fractions (Figs.…”
Section: Discussionmentioning
confidence: 38%
“…A number of turnover studies have suggested a correlation between rate of turnover and protein subunit size for rat liver soluble and membrane proteins (Dehlinger & Schimke, 1971Dice & Schimke, 1972;Dice et al, 1973;Wang & Touster, 1975;Dean, 1975). In this study no such correlation can be seen in any of the submitochondrial protein fractions (Figs.…”
Section: Discussionmentioning
confidence: 38%
“…An alternative explanation is that the rapid labelling could be a result of a specific induction of the lysosomal system by Triton WR-1339 treatment. It has been reported that Triton WR-1339 leads to an induction of cathepsins B and D in rat liver (Dean, 1975). We have found that ATPase activity also increases after Triton WR-1339 treatment (Table 3); however, N-acetyl-fl-D-glucosaminidase activity did not increase.…”
Section: Discussionmentioning
confidence: 54%
“…This description of the turnover of lysosomalmembrane proteins can also accommodate the observation that they do not show a clear correlation between subunit size and half-life (Dean, 1975b;Wang & Touster, 1975), unlike endoplasmic-reticulum-membrane proteins. During digestion in vitro ofsoluble proteins by lysosomal or other proteinases, those of short half-life in vivo (which are enriched in large-subunit proteins) are degraded fastest.…”
mentioning
confidence: 77%
“…In the case of autophagy by lysosomal invagination, cytosol proteins are sequestered (Dean, 1975a), but this process should also result in degradation of lysosomal membrane, apparently as a unit. However, it is clear that lysosomal-membrane proteins have quite heterogeneous half-lives (Dean, 1975b;Wang & Touster, 1975). If invagination and unit degradation accounted for a large part of lysosomal-membrane turnover, this observation would be difficult to explain.…”
mentioning
confidence: 99%